SEEING BETTER ON THE LEVEL OF LAMPS: PERCEPTUAL NORMATIVITY IN MERLEAU-PONTY - Wall, Emily A. (My University, 2019)
This thesis develops an interpretation of Merleau-Ponty’s existential-phenomenological conception of perceptual normativity, that is, how there are norms, internal to perception itself, governing our everyday perceptual involvements with the world. I argue that Merleau-Ponty conceives perceptual norms as being gestalt-structural forms of ‘original sense’, which we experience pre-reflectively in a direct, bodily way. I motivate my interpretation by examining a passage in Phenomenology of Perception where Merleau-Ponty remarks on how perception tends toward an optimal or better view of things, indicating a normative dimension in perception. I make sense of this passage in relation to Merleau-Ponty’s wider gestalt-ontological thought about embodied subjectivity. I unpack how, via the basic intentional structure of perspective by which subject is geared into the perceptual world, body-subject adopts an ‘original sense’ or ‘look’, which undergoes an open process of definition that is experienced as normative. This account can further clarify some questions Merleau-Ponty does not explicitly address about our lived experience of perceptual norms: namely, how perceptual norms are temporal and contingent in their hold on body, and how these norms integrate the subject’s perceptual interests. I further investigate how perceptual norms, in the context of Merleau-Ponty’s thought, are perceived in a two-fold or ambiguous way: the subject lives norms immediately from the ‘inside’, but can also adopt a perspective on norms. In so doing, the subject can perceive the norm itself from the ‘outside,’ which is to partially ‘free’ body from the world’s normative grip. This interpretation is presented as a response to a debate in the literature involving Sean Kelly, Corinne Lajoie, and Samantha Matherne on how Merleau-Ponty conceives perceptual normativity.
Keywords: Perception; Normativity